2023
DOI: 10.1002/hbm.26237
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment and retinal and brain neurodegeneration: A population‐based study

Abstract: Visual impairment and retinal neurodegeneration are intrinsically connected and both have been associated with cognitive impairment and brain atrophy, but the underlying mechanisms remain unclear. To investigate whether transneuronal degeneration is implicated, we systematically assessed the relation between visual function and retinal, visual pathway, hippocampal and brain degeneration. We analyzed baseline data from 3316 eligible Rhineland Study participants with visual acuity (VA), optical coherence tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…A pathophysiological relationship appears to exist between regions involved in sensory processing and diabetic peripheral neuropathy severity, 22 neuropathic pain 4 and worsening visual impairment in diabetic retinopathy. 23 Previous studies reported structural alterations in the central nervous system in T1D 24 and T2D. 25 26 This was demonstrated in a large cohort of deeply phenotyped participants with diabetes, where mild cognitive impairment prevalence was comparable to age-adjusted rates of the general population despite accelerated incipient cognitive decline.…”
Section: Discussionmentioning
confidence: 91%
“…A pathophysiological relationship appears to exist between regions involved in sensory processing and diabetic peripheral neuropathy severity, 22 neuropathic pain 4 and worsening visual impairment in diabetic retinopathy. 23 Previous studies reported structural alterations in the central nervous system in T1D 24 and T2D. 25 26 This was demonstrated in a large cohort of deeply phenotyped participants with diabetes, where mild cognitive impairment prevalence was comparable to age-adjusted rates of the general population despite accelerated incipient cognitive decline.…”
Section: Discussionmentioning
confidence: 91%
“…However, visual acuity was not associated with any brain MRI measures, in contrast to another study. (38) Myopia was associated with decreased risk of dementia in observational models. Although this is consistent with some prior work,(54) we believe this is likely due to residual confounding, as the Myopia-GRS was not associated with all-cause dementia, AD, or VaD.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings are strengthened by evaluating multiple ADRD-related outcomes including neuroimaging makers. Few prior studies have examined associations between vision and ADRD-related neurodegeneration (38,39,52). In our study, cataracts were associated with increased brain atrophy, including total grey matter and occipital volumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because dopaminergic cells—RGC and amacrine cells (ACs)—reside in these layers and are principal cells involved in PD. 10 …”
Section: Introductionmentioning
confidence: 99%